ПРИСТРОЇ КОРИГУВАННЯ ФОРМИ НАПРУГИ МЕРЕЖІ, ЯКА ЖИВИТЬ НАПІВПРОВІДНИКОВИЙ КЕРОВАНИЙ ВЕНТИЛЬНИЙ ВИПРЯМЛЯЧ ЗІСТАВНОЇ З МЕРЕЖЕЮ ПОТУЖНОСТІ - Чиженко, O.І. (Інститут електродинаміки Національної академії наук України, 2024)
The paper investigates the application of a technical method of volt-addition in converters designed to correct the voltage waveform of the network supplying a powerful controlled valve rectifier of comparable power to the supply network. A modification of the circuit of a known converter with a diode rectifier adapted for the case of supplying a controlled rectifier and for correcting the voltage waveform at its input is considered, and its shortcomings are indicated. The original effective circuit and technical solutions of devices for correcting the shape of the mains voltage using the method of volt-addition are presented. In the first solution, the device is powered from the auxiliary power supply, and in the second, more universal, it is powered directly from the mains transformer.  Ref. 7, fig. 3.